9 - Narratives of Zimbabwean female teachers’ experience in South Africa - Zvisinei Moyo (African Sociological Review, 2021)
The violent political situation and economic meltdown in Zimbabwe at the turn of the 21st century that saw a mass exit of Zimbabweans to other countries served as a catalyst for this study. Female teachers were among the historic outflow to neighbouring South Africa. Thus, this paper examined the experience of Zimbabwean female immigrant teachers in South Africa. Empirically, narrative interviews, were used together to elicit data. The author who was amongst the immigrant teachers gave a narration of her story. The interviews were electronically recorded and transcribed verbatim. Data were analysed using the feminist critical discourse perspectives. The key findings speak to female immigrant teachers as resilient professionals who were able to overcome the challenges of resettling in South Africa. Zimbabwean female immigrant teachers have challenged prevailing stereotypes for instance that male dominance. Therefore, the South African government needs to enact policies that improve the plight of female immigrant teachers.